Technique for confidence interval calculating for estimating of the random value subordinated to the composition of normal and uniform distributions - E. L. Kreidik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The general case of determining of probability of hit by a given section of a random variable subordinated to the composition of normal and uniform distribution laws having arbitrary distribution centers is considered. A technique for confidence interval calculating for estimating of the random value subordinated to the composition of normal and uniform distributions is proposed.